2010
DOI: 10.1128/mcb.01056-09
|View full text |Cite
|
Sign up to set email alerts
|

The UBXN1 Protein Associates with Autoubiquitinated Forms of the BRCA1 Tumor Suppressor and Inhibits Its Enzymatic Function

Abstract: Although the BRCA1 tumor suppressor has been implicated in many cellular processes, the biochemical mechanisms by which it influences these diverse pathways are poorly understood. The only known enzymatic function of BRCA1 is the E3 ubiquitin ligase activity mediated by its highly conserved RING domain. In vivo, BRCA1 associates with the BARD1 polypeptide to form a heterodimeric BRCA1/BARD1 complex that catalyzes autoubiquitination of BRCA1 and trans ubiquitination of other protein substrates. In most cases, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…Knockdown of VCP/p97 in the reporter assay indicated that VCP/p97 is simply not involved in UBXN1-mediated NF-B inhibition. Another study (24) revealed that UBXN1 may block the function of BRCA1 by directly binding the ubiquitin chain. In our data, UBXN1 interacts with cIAPs through the UBA domain and prevents the interaction between TRAF2 and cIAPs as the negative regulator of NF-B signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of VCP/p97 in the reporter assay indicated that VCP/p97 is simply not involved in UBXN1-mediated NF-B inhibition. Another study (24) revealed that UBXN1 may block the function of BRCA1 by directly binding the ubiquitin chain. In our data, UBXN1 interacts with cIAPs through the UBA domain and prevents the interaction between TRAF2 and cIAPs as the negative regulator of NF-B signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 participates in tumor suppression and its ubiquitin ligase activity has a significant role in this tumor suppression [127]. Therefore, UBXN1 may facilitate tumor progression by negative regulation of BRCA1 [128]. UBXN1-dependent inhibition of pro-survival protein cIAP1 and tumor suppressor protein BRCA1 suggests a controversial role for UBXN1 cancer.…”
Section: Ubxn1 An Inhibitor Of Cellular Inhibitors Of Apoptosis mentioning
confidence: 99%
“…Ubiquitination with K6-linked chains occurs on the BRCA1-BARD1 Ub ligase and its associated substrates, suggesting a link to DNA repair processes (Wu-Baer et al, 2010). K11-polyUb may interact with the Npl4 adaptor protein during Drosophila development, among other roles associated with the mitotic phase in the cell cycle and ERAD (Meyer and Rape, 2014; Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%